PERJANJIAN PEMBIAYAAN HUNIAN SYARIAH DENGAN AKAD MURABAHAH DAN MUSYARAKAH PADA PT. BANK MUAMALAT INDONESIA, TBK. CABANG JAMBI - Syarifa Mahila (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Type consumer financing PT.BMI Tbk. Branch Jambi one form of mortgage financing Muamalat iB is a product that will help people to have a home (ready stock / ex), apartments, shops, shophouse, kiosks take-over or transfer of mortgages from banks other. Based on Islamic principles with two choices murabahah (sale and purchase) or mutanaqishah Musharaka (partnership leases).Musharaka contract Mutanaqisah emphasis on the use of sale and purchase agreement with shirkah and reduction of one part (portion) shirkah with rental. Cooperation is done in terms of equity ownership or funding and cooperation. While the lease is the compensation given one party to another.Residential Financing Murabahah Syariah, Bank to buy first home customers want from the developer or the home seller. After that the house will be handed over to the customer with a purchase contract, then the customer will pay monthly installments in accordance with the agreed notional principal contract early.Implementation of the agreement on Murabahah PHS and PHS with a Musharaka contract Mutanaqisah (MMQ) using umbrella sharia law and legislation in the form of legislation or in the form of Bank Indonesia Regulation. Rights and obligations of each party are clearly stated in the agreement that has been agreed upon by both parties.Keywords : Financing, Contract  Murabahah, Musharaka contract Mutanaqisah.